Lima Strategi untuk Meningkatkan Kualitas Pembelajaran di SMA Budi Mulia Karawang: Penelitian - Agus Purwanto; Farhan Amrilah Ahmad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Abstract With the education report card, the problems related to the quality of education in schools are clearly visible. The problems that currently exist at SMA BUDI MULIA that need to be improved are: quality of learning, numeracy skills, PMM usage activities, With the independent curriculum being a challenge in itself in order to direct diverse human resources in schools and mobilize learning communities. In improving the quality of education in schools, based on the education report card improvement program, the author created five mentoring programs with the term "BELISAMPO", namely: Education Report Card Review, Lesson Study, In House Training, Connecting Teachers and PMO Sharing. From the five programs carried out at school, changes emerged, including the implementation of routine lesson study activities, the formation of teacher community activities both in sharing good practices and using PMM. Several teachers have taken real action and received certificates. Then we conducted dissemination through the MGMP and FKSS communities. One of them is the formation of a lesson study community between schools.